Volume 11, Issue 1 (Winter 2021) PTJ 2021, 11(1): 13-24 | Back to browse issues page 10.32598/ptj.11.1.412.3 XML Print Download citation: BibTeX | RIS | EndNote | Medlars | ProCite | Reference Manager | RefWorks Send citation to: Mendeley Zotero RefWorks Daneshjoo A, Mousavi Sadati S K, Pourahmad F. Effect of Corrective Exercise vs Corrective Games on Upper Crossed Syndrome in Female Students. PTJ. 2021; 11 (1) :13-24 URL: http://ptj.uswr.ac.ir/article-1-451-en.html Effect of Corrective Exercise vs Corrective Games on Upper Crossed Syndrome in Female Students - Abdolrasoul Daneshjoo; Seyed Kazem Mousavi Sadati; Fahimeh Pourahmad (Physical Treatments: Specific Physical Therapy Journal, 2021)
Purpose: This study aimed to compare the effect of corrective exercise and corrective games on upper crossed syndrome in female students. Methods: This was a quasi-experimental study performed with the pre-test and post-test method. The study sample consisted of 60 people who were selected purposely, based on inclusion and exclusion criteria and the rate of the disorder. In the study sample, the mean±SD of age, height, and weight were 14.16±1.08 years, 133.49±5.59 cm, and 44.73±8.24 kg, respectively. The study samples were randomly assigned into three groups: corrective exercises group (n=20), corrective games group (n=20), and control group (n=20). Students with upper extremity syndrome were first identified through checkered screening and the New York test. Then, the subjects of both intervention groups performed the selected training programs for eight weeks, based on the defined protocols. Finally, the one-way ANOVA, paired t-test, and Bonferroni post hoc test were used to compare the between-group differences. Also, the significance level was considered as P